2020
DOI: 10.2478/njmr-2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

In-Between Space/Time: <i>Affective Exceptionality during the ‘Refugee Crisis’ in Northern Finland</i>

Abstract: This article analyses the 'European refugee crisis' in the context of Northern Finland, building on the concepts of exceptionality and affect. Conventionally, exceptionality is conceptualised from the perspective of the state that does not enable analysing exceptional situations in their broader social context. A shift in focus is required to understand how people perceive and experience exceptionality and what kinds of affects this involves. Based on participatory engagement and in-depth interviews with asylu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Finland received an exceptional influx of asylum seekers in 2015 because of the so-called "refugee crisis" in Europe. This brought both challenges and possibilities to Northern Finland, where immigration in this form and to this extent was a new phenomenon (Clarke, 2009;Seppälä, Nykänen, Koikkalainen, Mikkonen, & Rainio, 2019).…”
Section: Research Methods and Data: A Participatory Theatre Workhop mentioning
confidence: 99%
See 1 more Smart Citation
“…Finland received an exceptional influx of asylum seekers in 2015 because of the so-called "refugee crisis" in Europe. This brought both challenges and possibilities to Northern Finland, where immigration in this form and to this extent was a new phenomenon (Clarke, 2009;Seppälä, Nykänen, Koikkalainen, Mikkonen, & Rainio, 2019).…”
Section: Research Methods and Data: A Participatory Theatre Workhop mentioning
confidence: 99%
“…The research encounters were linked to a specific time and space. This created research relationships and knowledge that were bound spatially and temporarily to Northern Finland, in the time of tightened immigration policy since the 2015 "flow" of asylum seekers (Seppälä et al, 2019), while simultaneously increasing societal divisions (e.g., ethnic and cultural) and diversifying society and communities. Addressing the temporal-spatial context of the art-based research as part of the process established access to deeper knowledge and interaction than conventional research methods usually enable.…”
Section: Temporal-spatial Contextmentioning
confidence: 99%
“…For this reason, we do not focus the analysis of reactions to the crisis on formal policy, but on the affective moods among European citizens produced by the ongoing incapacity of official politics to deal with this global humanitarian collapse. Refugees experience a process of affective exceptionality (Seppälä et al 2020), inhabiting an in-between space-time, a transformational situation in which the sense of normalcy becomes radically disrupted. Consequently, this socio-political crisis articulates a vast landscape of places of exceptionality where refugee camps, border walls, maritime blockages, quasi-penitentiary internment camps and countless dead bodies behave as socio-spatial heterotopias.…”
Section: Politics Of Care and Intimate Design Practices In Crisis-rid...mentioning
confidence: 99%
“…Por esta razón, no centramos el análisis de las reacciones a la crisis en las políticas formales, sino en los estados afectivos de los ciudadanos europeos producidos por la actual incapacidad de las políticas oficiales de lidiar con este problema humanitario global. Las personas refugiadas experimentan un proceso de excepcionalidad afectiva (Seppälä et al 2020) porque viven en un espacio-tiempo a medias, una situación transformativa en la que el sentido de la normalidad queda muy perturbado. En consecuencia, esta crisis sociopolítica articula un gran paisaje de lugares de excepcionalidad, en los que los campos de refugiados, los muros fronterizos, los bloqueos marítimos, los campos de internamiento casi penitenciarios y los incontables cadáveres se comportan como heterotopías socioespaciales.…”
Section: Políticas Del Cuidado Y Prácticas íNtimas De Diseño En Conte...unclassified
“…During the 2010s, attention has been paid especially on men's role in families (Author's own), parenting support and declining birth rate (Sihvonen, 2020). When the interviews for the study reported in this article were gathered, public attention was paid especially on immigrant families and families of same-sex parents, mainly due to the European refugee crises in 2015 and the law allowing same-sex marriages taking effect in early 2017 (for more information on the European refugee crisis in Finland, see Seppälä et al, 2020; on the gender neutral Finnish Marriage Act, see Lahti, 2019, p. 17).…”
Section: Public Interest In Family Lifementioning
confidence: 99%